Akad Musyarakah As Productive Waqf Aspect To Optimizing Ar-Rahman Mart According To Fatwa DSN-MUI : English - Lahuri, Setiawan Bin; Arti, Dwi Karunia (ASFA Foundation, 2024)
Growing of efficient waqf it's also done by means of participating with third parties, supported by issuance of the DSN-MUI Fatwa number: 08/DSN-MUI/IV/2000. So, the study aims to determine how the practice of akad Musyarakah at Ar-Rahman Mart and how the practice of akad musyarakah in perspective of Fatwa DSN-MUI No: 08/DSN-MUI/IV/2000 at Ar-Rahman Mart (ARM). This research is qualitative research with the type of case study through method of interview and documentation. The results obtained are the practice of akad musyarakah at Ar-Rahman Mart use musyarkah or Franchise system or KASOEIBI (Sharing Economic Cooperation or Kerjasama Ekonomi Berbagi) for 5 years beginning in 2019, profit sharing is 9:1 for CV Ar-Rahman and Alfamart, cause this cooperation have same goals to increasing society economic and in Ar-Rahman Mart produce waqf wealth to convert Masjid through profit motivation. The franchise system has principle of openness and prudence by sharia principles, but unfortunately, its contract does not fulfill all rules contained in the DSN-MUI Fatwa, this is because both parties have provided capital, but in the management and operation that occurred at Ar-Rahman Mart, the Ar-Rahman Foundation and CV Ar-Rahman did not have the authority to control the business activities in Ar-Rahman Mart every day.